Socjotechnika antykonsumpcji w warunkach globalizacji - Łukasik, Mariusz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The efficiency of activities related to the sociotechnics of anti-consumption is crucial to maintain the stability of a modern democratic system. This is of course, if we assume that the present direction of changes which establish the social and economic factors of life of societies (mainly the polarization of material status of various social groups) will be maintained. If the present tendency was to be reversed the activities related to the sociotechnics of anti-consumption would not be necessary, at least to the extent required at present. Then, the anti-consumption attitude would be likely to return to its original form, and it would again become the expression of protest against the social order, or a whim of elite groups.